PENGEMBANGAN MEJA LIPAT BELAJAR MULTIFUNGSI MENGGUNAKAN METODE QUALITY FUNCTION DEVELOPMENT (QFD) - Zainudin, Muhamad; Kusaeri, Didi; Susanti, Susi (Jurnal Riset Rumpun Seni, Desain dan Media, 2022)
Study table is one of the supporting learning activities but the current study table design is not in accordance with consumer needs, especially for children. The development of this study table product is expected to answer the needs of custumers or consumers and produce an ergonomic study table. This multifunctional learning folding table product uses the parameter measurement of the Quality Function Deployment (QFD). The result obtained based on the customer show that there are 7 attributes (customer requitment) and 4 technical parameters ( technical response). In this regard, the product development of a multifuntional folding study table uses the Quality Function Deployment (QFD) method using teak wood. This table also has several features, namely a reading light feature, a glass holder, a storange feature, equipped with a simple design, attaractive practical colors and ideal dimensions so as to increase comfort inusing the folding study table product.